Global Research Hotspots in Venous Thromboembolism Anticoagulation: A Knowledge-Map Analysis from 2012 to 2021 - Jia Wang; Yang-Xi Liu; Yi-Dan Yan; Li Liu; Chi Zhang; Mang-Mang Pan; Hou-Wen Lin; Zhi-Chun Gu (Journal of Interventional Cardiology)
Background. Venous thromboembolism (VTE) is a common cardiovascular disease that seriously threatens human lives. Anticoagulant therapy is considered to be the cornerstone of VTE treatment. An increasing number of studies has been updated in the VTE anticoagulation field. However, no bibliometric analyses have assessed these publications comprehensively. Therefore, our study aimed to analyze the global status, hotspots, and trends of anticoagulant therapy for VTE. Methods. The relevant literature on VTE anticoagulation published between 2012 and 2021 was retrieved and collected from the Web of Science Core Collection database. VOSviewer, Cooccurrence Matrix Builder, gCLUTO, and some online visualization tools were adopted for bibliometric analysis. Results. A total of 15,152 related articles were retrieved. In recent years, the research output of VTE anticoagulation gradually increased. The United States was the most productive country. International cooperation is concentrated in North America and Europe; the most influential documents, journals, authors, and organizations were also from these two continents. Research hotspots mainly focus on clinical guidelines, VTE in special populations, non-vitamin K oral anticoagulants (NOACs), and parenteral anticoagulation. The research frontiers and trends include the assessment of NOACs and the antithrombotic management of VTE complicated with coronavirus disease 2019 (COVID-19). Conclusion. This bibliometric analysis provides a systematic overview of the VTE anticoagulation research, which will facilitate researchers to better understand the situation of VTE anticoagulation. Future studies should be dedicated to NOACs application and VTE-combined COVID-19 patients.